Recent advances and opportunities for multi-robot systems in oceanography - Jessica C. Garwood; Xi Yu; Geoffrey A. Hollinger; Philip B. Lundrigan; Atsuhiro Muto; Nicholas R. Rypkema; Yu She (Frontiers in Marine Science, 2026)
Autonomous multi-robot missions are revolutionizing oceanographic data collection by increasing spatial coverage, mission durations, and allowing safe access to remote and dangerous environments at a fraction of the cost of ship-based missions. While terrestrial and aerial field robotics offer several approaches for multi-robot coordination, ocean applications present unique challenges — including navigation in a time-evolving, unknown, 3D fluid environment with significant drag, limited communications, and long-duration missions without opportunities to recharge — which require tailored solutions. To promote novel solutions arising from collaborations between field robotics and oceanography, we detail recent advances in terrestrial and aerial multi-robot coordination which we contextualize in relation to oceanographic needs, distinguishing applications at the ocean surface, at depth, and between the two domains. We conclude by highlighting future research opportunities, focusing on vehicle technology, underwater networking, and de-risking. We also emphasize that oceanographic and space missions share several similarities, making the ocean an excellent test bed for future developments.